Nutritional Evaluation of Indian Ocean Swimming Crab, Charybdis smithii (Portunidae), an Unconventional Crab Resource from the Indian Coast. Issue 2 (7th February 2019) - Yogesh Kumar, K.; Dineshbabu, A. P.; Thomas, Sujitha
ABSTRACT: Investigations were carried out to determine the nutritional profile of Indian Ocean swimming crab Charybdis smithii, which is emerging as an unconventional resource in trawl discards of India. The average protein content was 9.38 g/100 g, fat 0.86 g/100 g, ash 0.34 g/100 g, fiber 0.13 g/100 g, and carbohydrate 1.8 g/100 g. One-way analysis of variance showed no significant variations of constituents except in dry matter and carbohydrate between sexes. Macronutrients, Na (317.1, 327.6/100 g), K (148, 177.40 mg/100 g), Ca (187.90, 285.80 mg/100 g), and Mg (34.31, 41.49 mg/100 g), showed significant variation between sexes. The composition of micronutrients in male and female were Cu (0.28, 0.15 mg/100 g), Fe (0.57, 0.71 mg/100 g), and Zn (1.71, 2.75 mg/100 g). Mineral content showed significant difference between sexes. Amino acid analysis showed that 12.04 and 11.47 g/100 g essential amino acid glycine was present in male and female, respectively, and lysine concentration was 13.96 and 12.65 g/100 g, respectively. The nutritional profile of the species was determined the first time and shows that it is comparable with any other edible crabs and could be exploited as a commercial resource to supplement nutritional demand.